Didactic use of GIS and Street View for Tourism Degree students: understanding commercial gentrification in large urban destinations - Carlos Martínez-Hernández; Claudia Yubero; Elena Ferreiro-Calzada; Sofía Mendoza-de Miguel (Investigaciones Geográficas)
Tourism gentrification, as a complex phenomenon in large urban destinations, is an important topic for future tourism professionals. The aim of this paper is to offer a digital cartography making activity based on the contemporary dynamics of commercial transformation within tourism gentrification contexts in Madrid in order to facilitate its understanding. This innovative teaching activity is in accordance with the sustainable tourism pedagogy approach and follows an active methodology using three different GIS applications: Google Street View, ESRI ArcGIS Desktop and ESRI ArcGIS Online Story Maps application. A 4-phase methodological design is proposed so that the activity is customizable (1- recognition of previous ideas), achievable (2- significant streets’ mapping), collaborative (3- collective idea-sharing) and replicable (4- academic and didactic evaluation). Finally, the results from an initial implementation are brought to light: i) an initial conceptual lack was found, ii) examples that help to see the proposal materialized are shown and iii) expected positive consequences according to the scientific literature are presented. It is concluded that, despite the scarce bibliography, the use of GIS software and Google Street View in tourism higher education is convenient, not only to facilitate the learning of complex territorial phenomena but also to learn digital tools highly valued in the professional field.